The Role of Music in Predicting Academic Achievement: A Technological Discovery - Patricio K. Chap-as (Britain International for Academic Research (BIAR) Publisher, 2019)
This research undertaking aimed to find out the impact of instructional technology in teaching Music. Specifically, it was framed from the following context: 1. What is the mean performance of the controlled group and experimental group after the instructional technology was used in teaching Music?;2. What is the difference in the mean performance of the control group and experimental group after instructional technology was used in Teaching music? ;The researcher employed the experimental research method specifically the between-group design. From the results of the statistical computations, the following were revealed: The experimental group visibly performed better after instructional technology was integrated in teaching music than their control group counterpart. Findings of the study revealed there was a statistically significant differences in the academic achievement between the average mark of the experimental group students and the average mark of the control group students in favor of the experimental group.